DOCUMENT AND/OR THE GAZE OF POWER: “THE SIEGE” ARCHYVE - ARLAUSKAITĖ, NATALIJA (Politologija, 2013)
The article questions the order of contemporary film archive working with cinematic documents of mass extermination, dying and suffering. It scrutinizes how the forms of historical memory based on archive footage are constructed, what “acceptance” of these forms by general and professional public tells us about the collective identity of “acceptees” and the configuration of their historical memory. The main material is the World War II archive footage films, primarily films about the Holocaust and the Leningrad Siege.The general framework of the article is based on the question of historical memory forms and the peculiarities of its cinematic construction. It starts with the concept of (war) archive (Michel Foucault, Allan Sekula) and moves to the re-interpretation of visual documents from the WWII in the European experimental film and visual arts. Then it surveys the ways of conceptualizing the experience of witnessing / looking at the sites challenging the limits of humanity (Giorgio Agamben, Georges Didi-Huberman). Finally, it analyses in detail the film “The Siege” (2006) by Sergei Loznitsa, a “consensual” film in regard to the common understanding of “the truth of the blockade”.The analysis shows what the form of archive is created / supported by the narrative strategies of the film, first of all by the visual and sound montage, what kind of power position it transmits, and how this film answers the question about the meaning of the WWII representation in Russia today. Thus structured, the article “tests” whether the interpretative models and vocabulary of the “paradigmatic” – Holocaust – case in terms of visual representation are applicable / limited in discussing other cases of mass killing, dying, or suffering, here – the Leningrad blockade.The analysis of “The Siege” by Loznitsa shows that the historical memory consensus in the form of film (probably not only in Russia) pays its price: it engages into the retro-scenario (Jean Baudrillard, Thomas Elsaesser). It proves that archiving conventions are hardly to change significantly as long as the order of “witnessing” is grounded in the institutionally arranged archive and dominant modes of representation. Finally, “The Siege” demonstrates the validity and the limits of the Soviet version of the WWII cultural mythology still offering the ground for the collective positive identity: the WWII myth works until the enemies are punished and the Victory firework cast.